1981
DOI: 10.1017/s0043174500040182
|View full text |Cite
|
Sign up to set email alerts
|

Response of Vegetable Crops to Sublethal Application of 2,4-D

Abstract: Sublethal amounts of 2,4-D [(2,4-dichlorophenoxy) acetic acid] were applied to several vegetable crops in order to determine effect on yield and quality in a simulated drift experiment. Tomato (Lycopersicon esculentum Mill.) and root crops were most sensitive to 2,4-D; as little as 2.1 g/ha of acid distorted tomato fruit shape and elongated radish (Raphanus sativus L.) roots. All root crops were rendered unmarketable by 10.4 g/ha and gross yields were reduced by exposure to 104 g/ha. Yield of peppers (Capsicum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
2

Year Published

1984
1984
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 7 publications
2
40
0
2
Order By: Relevance
“…Before application and throughout the sampling period each season, plants from the untreated check had low concentrations of PGR residue present in foliage (Table 5). Other studies have reported positive PGR residue detection on control samples (Cessna, 1980; Hemphill and Montgomery, 1981; Smith, 1984). In addition, 10 random soybean samples taken in 2000 from fields that had no visual PGR injury symptoms had 2,4‐D detections ranging from 0.009 to 0.036 μg g −1 and three had positive dicamba detections (unpublished data, 2000).…”
Section: Resultsmentioning
confidence: 87%
“…Before application and throughout the sampling period each season, plants from the untreated check had low concentrations of PGR residue present in foliage (Table 5). Other studies have reported positive PGR residue detection on control samples (Cessna, 1980; Hemphill and Montgomery, 1981; Smith, 1984). In addition, 10 random soybean samples taken in 2000 from fields that had no visual PGR injury symptoms had 2,4‐D detections ranging from 0.009 to 0.036 μg g −1 and three had positive dicamba detections (unpublished data, 2000).…”
Section: Resultsmentioning
confidence: 87%
“…Few researchers have reported secondary shoot initiation or increased branching of flower species in response to low rates of plant growth regulators. Hemphill and Montgomery (1981) reported that 2,4-D at 2.1 g·ha -1 increased pep- per branching and flowering, which resulted in increased yield compared to the untreated crop. However, pepper was the only species of the 15 tested that responded in this manner.…”
Section: Resultsmentioning
confidence: 99%
“…Tomato sensitivity to auxin herbicides has been the subject of several published studies (Bennet 1989;Breeze and West 1987;Fagliari et al 2005;Hemphill and Montgomery 1981;Jordan and Romanowski 1974;Smith and Geronimo 1984;Van Rensburg and Breeze 1990). Visual symptoms can be observed at 1 to 2 g ae ha À1 of 2,4-D and gross yield reductions have been reported in the range of approximately 3 to 20 g ae ha À1 for plants in the flowering stage.…”
Section: Nontarget Plant Sensitivitymentioning
confidence: 99%
“…Other vegetable crops show a range of sensitivity to low rates of 2,4-D. Hemphill and Montgomery (1981) reported no significant yield effects on broccoli (Brassica oleracea var. italic L.), cabbage (Brassica oleracea var.…”
Section: Nontarget Plant Sensitivitymentioning
confidence: 99%